648 APPLICATION OF THE GLOBAL LEADERSHIP INITIATIVE ON MALNUTRITION (GLIM) CRITERIA IN PERIOPERATIVE MANAGEMENT OF ESOPHAGEAL CANCER PATIENTS. (17th September 2021) - Wang, Peiyu; Li, Yin; Liu, Xianben
Abstract:  : In 2019, the Global Leadership Initiative on Malnutrition (GLIM) established global malnutrition diagnostic criteria and classification methods. This study aimed to investigate the application of GLIM criteria in nutrition assessment and perioperative management in esophageal cancer patients undergoing esophagectomy. Methods: A prospective institutional database of 212 esophageal cancer patients was reviewed. The property of the GLIM criteria in diagnosing malnutrition and predicting adverse therapeutic outcomes were evaluated. The two-step approach of initially screening malnutrition risk with conventional tools and then establishing diagnosis and classification with the GLIM criteria was investigated. The candidate malnutrition screening tools include the Malnutrition Universal Screening Tool (MUST), the Nutritional Risk Screening 2002, the Short-Form of Mini Nutritional Assessment, and the Geriatric Nutritional Risk Index. Results: Among the included 192 patients, the proportions of moderate and severe malnutrition diagnosed by the GLIM criteria were 42.7% and 30.2% before surgery. In multivariable analyses, severe malnutrition was predictive of perioperative overall complications and major complications (both P < 0.001). Among the four candidates, malnutrition screened by the MUST showed highest sensitivity (90.7%), specificity (92.3%) and diagnosis consistency with the GLIM criteria. The two-step approach of MUST-GLIM showed comparable performance with pure GLIM criteria in predicting perioperative morbidities and survival outcomes, better than the conjunction of other three malnutrition screening tools with the GLIM criteria. Conclusion: The GLIM criteria should be highlighted in perioperative management of esophageal cancer patients. The MUST is the recommended initial malnutrition screening tool in implementing the GLIM criteria.